BeO Utilization in Reactors for the Improvement of Extreme Reactor Environments - A Review - Li, Kai; Qian, Libo; Li, Xiaojing; Ma, Yu; Zhou, Wenzhong (Frontiers in Energy Research, 2021)
Ceramic material is one of the essential materials used in reactors. Beryllium oxide ceramics have good high-temperature radiation stability, high density, high strength, and thermal conductivity at high temperatures, and the price of beryllium oxide is relatively moderate. This makes it more suitable for use as a reflector, moderator, and dispersion phase fuel matrix in a reactor. In recent years, beryllium oxide has attracted widespread attention due to its high hardness, high resistivity, high thermal conductivity, high melting point, and high radiation resistance. Because of its excellent mechanical properties, beryllium oxide materials also have a long history in the field of nuclear energy. Reactor extreme environments have become a significant challenge for optimizing reactor operation and safety performance. The utilization of beryllium oxide can significantly alleviate extreme reactor environments. According to research, the coupling of beryllium oxide material can effectively improve nuclear fuels' thermal conductivity, such as uranium dioxide. Beryllium oxide also has good radiation resistance and neutron scattering properties, which increases its applications in nuclear energy. The article comprehensively reviews the BeO utilization approaches in reactors to improve extreme reactor environments for current reactor operation and future reactor design optimization.